Design of Medicinal Plants in the Urban Landscape: A Prospect for the Future? - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail azlan (IIUM, 2009)
Abstract In day to day living aromatic and medicinal plants served as medicine, first aid relief, food and seasoning, cosmetic and dyes. In religious practices they provided talisman, mind altering substance for religious divinations. Today, these medicinal and aromatic plants are gaining popularity through kitchen garden, back to nature medical treatment and research grants. Since 60% of the Malaysian populations are living in the urban areas the feasibilities of these plants being part of the urban landscape around city suburbs will have a bright potential provide several effective, constructive and creative methods are implemented. This paper will explore the weakness and strengths in propagating ideas of designing the urban spaces with medicinal and aromatic aromatic plants and provide some suggestion in the implementation of the design of these plants in the urban landscape.